Gram Stain and Ziehl Neelsen Stain: Limited but Important, Specific Diagnostic Tool (Bangladesh Journal of Medical Microbiology, 2017)
Abstract not availableBangladesh J Med Microbiol 2017; 11 (2): 1-4